1998
DOI: 10.1111/j.1365-2109.1998.tb01135.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding Spirulina platensis on the growth, proximate composition and organoleptic quality of common carp, Cyprinus carpio L.

Abstract: The effect of feeding Spirulina platensis on the growth, carcass composition, organoleptic quality, digestive enzyme activity and digestibility of common carp, Cyprinus carpio L., was studied through a culture trial lasting 120 days. Four experimental diets were employed by replacing fish meal protein from the standard diet at 25%, 50%, 75% and 100% through the incorporation of Spirulina. Another diet with Spirulina as the sole source of protein was also used. The final weight gain, specific growth rate, food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(51 citation statements)
references
References 18 publications
(18 reference statements)
9
42
0
Order By: Relevance
“…Furthermore, our results are in agreement with that obtained by Dernekbasi et al, (2010) who evaluated the use of Spirulina in guppy diet and they found that increasing level of Spirulina in diet provided better growth comparing to the other commercial feeds. Nandeesha et al (1998) reported that body weight gain of Nile tilapia (O. niloticus) increased linearly with increasing the level of algae in fish diet.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results are in agreement with that obtained by Dernekbasi et al, (2010) who evaluated the use of Spirulina in guppy diet and they found that increasing level of Spirulina in diet provided better growth comparing to the other commercial feeds. Nandeesha et al (1998) reported that body weight gain of Nile tilapia (O. niloticus) increased linearly with increasing the level of algae in fish diet.…”
Section: Discussionmentioning
confidence: 99%
“…Spirulina Spirulina , (Nandeesha et al, 1998) Values (mean ± SE of replication group) in the same column not sharing a common superscript are significantly different (P<0.05). ns Not significant (P>0.05).…”
Section: 결과 및 고찰mentioning
confidence: 99%
“…carotenoids carotenoids , , , (Torrissen et al, 1989;Storebakken and No, 1992 Lee, 2012a, 2012b). carotenoids astaxanthin, zeaxanthin cantaxanthin (Matsuno et al, 1979;Nandeesha et al, 1998;Rema, 2005, Kim et al, 2008;Kim and Lee, 2012a). , , ,…”
Section: 서 론mentioning
confidence: 99%
See 1 more Smart Citation
“…They were studied in different fish species, breeds and hybrids (Hajinikolova and Grozev, 1996;Hajinikolova, 2004;Kocoura, et al, 2005) and under the conditions of different fish rearing technologies (Prikryl and Janecek, 1991;Nandeesha et al, 1998;Soliman et al, 2000;Papoutsoglou et al, 2001;Keshavanath et al, 2002;Nikolova, 2010;Varga et al, 2013).…”
Section: Introductionmentioning
confidence: 99%